A 5‐year retrospective audit of prescribing by a critical care outreach team. Issue 3 (15th December 2017) - Wilson, Mark
ABSTRACT: UK prescribing legislation changes made in 2006 and 2012 enabled appropriately qualified nurses to prescribe any licensed medication, and all controlled drugs in schedule 2–5 of the Misuse of Drugs Regulations 2001, for any medical condition within their clinical competence. Critical Care Outreach nurses who are independent nurse prescribers are ideally placed to ensure that acutely ill patients receive treatment without delay. The perceived challenge was how Critical Care Outreach nurses would be able to safely prescribe for a diverse patient group. This study informs this developing area of nurse prescribing in critical care practice. The aims of the audit were to: identify which medications were prescribed; develop a critical care outreach formulary; identify the frequency, timing and number of prescribing decisions being made; identify if prescribing practice changed over the years and provide information for our continuing professional development. This article reports on data collected from a 5‐year retrospective audit; of prescribing activity undertaken by nine independent nurse prescribers working in a 24/7 Critical Care Outreach team of a 600‐bedded district general hospital in the UK. In total, 8216 medication items were prescribed, with an average of 2·6 prescribed per shift. The most commonly prescribed items were intravenous fluids and analgesia, which were mostly prescribed at night and weekends. The audit has shown that Critical Care Outreach nurse prescribing is feasible in a whole hospital patient population. The majority of prescribing occurred after 16:00 and at night. Further research would be beneficial, particularly looking at patient outcomes following reviews from prescribing critical care outreach nurses. The audit is one of the only long‐term studies that describes prescribing practice in Critical Care Outreach teams in the UK.